LC-MS/MS-BASED METABOLOMIC CHARACTERIZATION AND ANTIDIABETIC POTENTIAL OF ETHANOLIC EXTRACT OF THE IPOMOEA MOMBASSANA VATKE STEM - LAKSHMI RAJITA KOTTA; VIJAYALAKSHMI A (Asian Journal of Pharmaceutical and Clinical Research, 2025)
Objectives: Ipomoea mombassana Vatke is a lesser-known species of the genus Ipomoea, with no prior reports on its phytochemical or pharmacological properties. This study investigated the phytochemical profile, enzyme inhibition, antioxidant activity, and antidiabetic potential of its stem extracts. Methods: Stems were successively extracted with solvents of increasing polarity, and yields were determined. The ethanolic I. mombassana stem extract (IMSE) was selected for detailed evaluation. Phytochemical screening was performed, and in vitro α-amylase and α-glucosidase inhibition assays (100–500 μg/mL) were carried out. Liquid chromatography-mass spectrometry (LC-MS/MS) analysis was conducted using an Agilent 1290 Infinity II LC system with 6550 iFunnel Q-TOF in positive electrospray ionization mode. In vivo activity was assessed in Streptozotocin-induced diabetic rats treated with IMSE (100 and 200 mg/kg) for 21 days, compared with normal, diabetic control (DC), and Metformin groups. Results: IMSE exhibited strong α-amylase (IC50=45.78±0.18 μg/mL) and α-glucosidase inhibition (42.26±0.97 μg/mL) compared to acarbose (34.4±0.56 and 32.95±0.45 μg/mL, respectively). LC-MS/MS identified 42 compounds, including pilocarpine, maritimetin, and ganoderic acid F. In vivo, IMSE significantly reduced fasting blood glucose from 344±1.6 mg/dL in DCs to 198±2.1 mg/dL at 200 mg/kg (p<0.001). It also improved lipid profiles by lowering total cholesterol, triglycerides, and low-density lipoprotein cholesterol while elevating high-density lipoprotein cholesterol (p<0.01–0.001). Liver enzyme levels were normalized (serum glutamate oxaloacetate transaminase: 71±1.6→52±1.1 U/L; serum glutamate pyruvate transaminase: 87±2.2→55±1.5 U/L; p<0.001). Antioxidant markers were restored, including superoxide dismutase (1.3±0.03→5.4±0.30 U/mL) and glutathione (0.32±0.056 → 1.7±0.069 mg/dL; p<0.001). Conclusion: The ethanolic extract of I. mombassana demonstrated significant enzyme inhibition and hypoglycemic effects, accompanied by improvements in lipid metabolism, hepatic function, and antioxidant defense, supporting its potential as a natural therapeutic for diabetes management.